Al-Farabi and Said Nursi on the civilising mission of the prophets - Akhmetova, Elmira (IIUM Press, International Islamic University Malaysia, 2017)
This paper studies the role of prophethood in building a civilisation with special reference to the writings of Al-Farabi and Said Nursi. In order to elucidate the thought of Al-Farabi, the ideas of Ibn Sina are consulted in some parts of the paper. The fi rst part of the paper defi nes the term “true civilisation” (or an “ideal state” according to Al-Farabi), its foundations and peculiarities from the viewpoints of these three Muslim scholars. I t suggests that, on one hand, a human being cannot achieve his main goal, i.e. felicity, without living in a society, and, on the other, his most fundamental need is the need for religion, revealed by the prophets. Therefore, these three scholars argued that the real civilisation, which can make its citizens happy, satisfi ed and equal without any exception, originates from divine laws. As paper fi nds, Said Nursi articulated that the mission of the prophets, besides establishing of the worship to One God, also includes bringing of economic and political justice, social stability, ethical enhancement and emotional inspiration to his society, which are the fundamental requirements for the building of strong civilisations but beyond the power of an ordinary man. Based on the ideas of the scholars, the paper concludes that, according to the Muslim scholars, the prophets sent by God were the best law-givers and founders of the most excellent civilisations.